Effects of new antiseizure medication on bone metabolism and bone mineral density in children: A meta-analysis - Zhuo, La; Zhang, Yong (Frontiers in Pediatrics, 2022)
Objective To explore the effect of new antiseizure medication on bone metabolism and bone mineral density in children. Methods The Chinese and English databases (PubMed, EMBASE, Cochrane Library, CNKI, Wanfang and VIP) were systematically searched for observational studies evaluating the effects of new antiseizure medication on bone metabolism and bone mineral density in children with epilepsy. The effects of new antiseizure medication on serum calcium, phosphorus, alkaline phosphatase, bone alkaline phosphatase, parathyroid hormone, 25-hydroxyvitamin D and bone mineral density in children were systematically evaluated. Results After systematic retrieval and screening, 12 studies with high literature quality (including 629 epileptic children and 627 control subjects ) were included in the systematic evaluation. Meta-analysis showed that new antiseizure medication decreased bone mineral density (MD: -0.05, 95%CI: -0.09, -0.02; P=0.004). From different kinds of antiseizure medication, levetiracetam can reduce blood phosphorus concentration in children (MD: -0.04; 95%CI: -0.07, -0.01). Oxcarbazepine increased serum alkaline phosphatase in children (MD:17.98; 95%CI: 10.43,25.53; P<0.00001), and the increase intensity was significantly higher than that of levetiracetam (MD: 7.66; 95%CI: 0.29, 15.02; P=0.04). In addition, oxcarbazepine can cause a significant increase in parathyroid hormone in children (MD: 7.52; 95%CI: 3.37,11.66; P=0.0004 ), and 25 - hydroxyvitamin D was reduced, and the difference was statistically significant (MD:−2.18; 95%CI : -3.23, -1.13; P=0.00006). However, the effects of new antiseizure medication on serum calcium and bone alkaline phosphatase in children were not statistically significant. Conclusion New antiseizure medication have different effects on bone metabolism and bone mineral density in children with epilepsy, and the effects of different types of new antiseizure medication are different.